Nutrition acquisition by human immunity, transient overnutrition and the cytokine storm in severe cases of COVID-19. (October 2021) - Yu, Boxuan; Yu, Ligen; Klionsky, Daniel J.
Abstract: The human immunity has a pivotal role in nutrition acquisition from the pathogens and damaged body tissue during the SARS-CoV-2 virus infection, which may lead to transient overnutrition in the patients, lead to lipotoxicity and further damage in non-adipose tissues, and cause hyperinflammation and cytokine storm in severe cases of COVID-19. In view of this, high-quality clinical trials on restrictive eating should be designed to investigate the possible benefits of food intake restriction on patients' recovery from COVID-19 disease.